Actual problems of building computer networks - Petrushenko, Daniil; Bykova, Tetiana (Bulletin of V.N. Karazin Kharkiv National University, series «Mathematical modeling. Information technology. Automated control systems», 2023)
Relevance: In connection with the growing use of computers and the Internet in the modern world, the construction of computer networks is an important task. However, there are various challenges that need to be addressed in order to build efficient and secure networks.Purpose: This article is devoted to an overview of current problems of building computer networks and methods of their solution.Research methods: To write this article, an analysis of literary sources was carried out and the experience of practical work in building computer networks was considered.Results: As a result of the analysis, it was found that the main problems of building computer networks are security, scalability, fault tolerance, efficiency and compliance with user requirements. To solve them, various technologies and tools for building and administering networks were considered.Conclusions: Building computer networks is an important task in today's world, there are several problems that need to be solved to ensure efficient and secure network operation. Various methods are used to solve them, which help to improve the quality and reliability of networks. This article considered individual problems of building computer networks, as well as an example of a solution to one of them, namely, network load analysisKeywords: computer networks, security, scalability, fault tolerance, efficiency, protection, encryption, firewalls, protocols, algorithms, duplication.